Studi Kapabilitas Proses Tablet Thiamazole 100 mg pada Salah Satu Industri Farmasi di Jawa Barat - Kaila Keyshia Mei; Holis Abdul Holik (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
The quality of a product needs to be maintained throughout its life cycle so that the quality remains consistent to the consumers. Therefore, regular quality control is needed to maintain quality according to predetermined specifications. To be able to maintain product quality, quality control is carried out using the Six Sigma method with DMAIC stages (Define, Measure, Analyze, Improve, Control). The purpose of this study was to determine the reproducibility of 10 mg Thiamazole tablet product which can be considered in determining the bypass status of the product at certain stages of testing, to determine the capability of the production process, and to analyze Thiamazole tablets. The results showed that the specification requirements and control limit range requirements. At the printing and coating stages the assay has Cpk value > 1, so that it can be considered the application of bypass status, but at the mixing and coating stages the dissolution has Cpk value < 1 which indicates that the process does not yet have a good value trend. This can be caused by several factors, for example personnel factors, machines, materials and methods at the stage of analysis of content and production.